Deep Learning in Early Childhood Education: A Systematic Review of Mindful, Joyful, and Meaningful Pedagogical Integration in the Indonesian Context - Tri Miftakhul Jannah, Bunga; Vera Yuliana, Dwi; Putri Yuniar, Dias (Nak-Kanak: Journal of Child Research, 2026)
Background of the study: Early Childhood Education (ECE) is a foundational developmental stage shaping cognitive and socio-emotional growth. However, instructional practices in many contexts—particularly in developing countries—remain dominated by surface-learning approaches that emphasize memorization over conceptual understanding and reflection. Although deep learning has gained prominence in educational discourse, its integration within early childhood pedagogy remains conceptually fragmented and insufficiently synthesized. Aims and scope of paper: This study aims to systematically review and synthesize theoretical and empirical evidence on the implementation of deep learning in Indonesian Early Childhood Education. Methods: A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Peer-reviewed journal articles published between 2015 and 2025 were retrieved from Scopus, Web of Science, ERIC, and Google Scholar databases. After applying inclusion and exclusion criteria, 42 eligible studies were analyzed using thematic synthesis to identify conceptual patterns, pedagogical strategies, and developmental outcomes associated with deep learning practices in early childhood settings. Results: The findings reveal that effective deep learning implementation in ECE relies on the dynamic integration of three interdependent pedagogical pillars: (1) mindful learning, characterized by reflective awareness and metacognitive engagement; (2) joyful learning, grounded in emotionally supportive and play-based pedagogy; and (3) meaningful learning, emphasizing contextualized and experience-based knowledge construction. Project-Based Learning (PjBL), guided play, collaborative inquiry, and sensory-motor exploration emerged as dominant instructional strategies supporting these pillars. Evidence across studies indicates positive associations between integrative deep learning approaches and improvements in self-regulation, problem-solving, social competence, and early cognitive flexibility. Contribution: This review advances the literature by conceptualizing deep learning as an integrated early childhood pedagogical framework that unites cognitive, emotional, and contextual dimensions of learning. It synthesizes fragmented constructs into a coherent model relevant to the Indonesian context and provides an evidence-informed reference for transitioning from outcome-driven instruction to reflective and developmentally responsive pedagogy.